Busting the myth that pilots never scale: Unpacking the USAID climate services for resilient development strategy in LAC - Prager, Steven D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presented by Steven Prager (Principal Scientist for Integrated Modeling) on 13 February 2020 at the 6th International Conference on Climate Services held at the Indian Institute of Tropical Meteorology (IITM). (https://www.climate-services.org/iccs/iccs-6/)